EL PERÚ QUE NO CONOCIÓ CERVANTES - Millones, Luis (2005)
As a way of avoiding social uneasiness in Spain, Cervantes, as manyothers, was eager to come to America. The existénce of sorne burocratricposts attracted his interest but, unfortunately, his applications were turneddown. He might not have been aware ofthe Indies' intricate problems buthe did know what a public office meant, :;ts it is shown in his wonderfuldepiction of Sancho, made governor of the ínsula Barataria. Besides,having ever set foot in America, the Indies appear recurrently in his works,although he expresses very general views about the new continent.